MASALAH SOSIAL DAN SOCIAL DEMAND DALAM AKSESIBILITAS PENDIDIKAN - Omon Abdurakhman; Irman Suherman; RSP Fauziah (TADBIR MUWAHHID, 2019)
Mean Years School (MYS) Bogor district in 2018 amounted to 7,82 years. Means to obligated learn 9 year in Bogor district to 2018 not yet reached. Moreover, if looking policy 12 years in obligated learn of base education. The big mission for district governance to upgrading education level as effort to creat Indonesian excellent human resources. Knowing to cause of drop out or unable of society to educational access is very important, in order to find best solutions of solve the problem it. The research objective is create schematic for explain to cause of drop out in Bogor district. It use survey method to 11 subdistrict with amount 184 people respondent. The result it is cause of drop out or unable to educational access in Bogor district, 1) Educational costs are unaffordable, 2) Interest to join traditional pesantren is very high, 3) More choose to work, cause to aid family economic, 4) bullying in school, 5) the child don’t school interest, 6) bad social intercourse, 7) a women; more choose is married, and 8) the opinion of social environmental is unembarrassing, if no schooling. The highest cause is why people drop out or unable to educational access is educational costs are unaffordable.